Impact of Agile Organization and Leadership on Employee Experience: Case Study UPTD (Technical Implementing Service Unit) Digital Service Center, Geospatial Data and Information of West Java Provincial Government (Jabar Digital Service) - Ridhwan Adhikersa; Wahyudi Kumorotomo; Achmad Djunaedi; Agus Heruanto Hadna (Populasi, 2022)
This research is a mixed study that analyzes the implementation of agile organization and agile leadership, and analyzes the impact of its implementation on employee experience at the Technical Implementing Service Unit Digital Service Center, Geospatial Data and Information of West Java Provincial Government called Jabar Digital Service (JDS) This research was conducted by searching for information on civil servants (PNS) and ex- pert employees about organizational and leadership methods applied in Jabar Digital Service. Concepts of agile organization and agile leadership and researching quantitatively the perception of employee experience of expert employees on the implementation of agile conceptions to organization and leadership in Jabar Digital Service using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) method was compared. This study shows that the implementation of agile organization and agile leadership can be applied in government organizations that are in fact rigid about change which is also shown by the level of positive perception of expert employees on the employee experience in the Jabar Digital Service environment.